Since \( JL \) is the perpendicular bisector of \( KM \), it means that:
- Point \( J \) is the midpoint of \( KM \).
- The lengths from \( K \) to the midpoint \( J \) and from \( J \) to \( M \) are equal.
Therefore, we have:
\[ KH = HM \]
Given that \( KH = 6y + 3 \) and \( HM = 27 + 7 = 34 \), we set these equal to each other:
\[ 6y + 3 = 34 \]
Now, we will solve for \( y \):
- Subtract 3 from both sides:
\[ 6y = 34 - 3 \] \[ 6y = 31 \]
- Now, divide by 6:
\[ y = \frac{31}{6} \]
Even though we have found \( y \), we also need to find HM:
From the earlier equation for \( HM \):
\[ HM = 34 \text{ units} \]
Thus, the length of segment \( HM \) is:
\[ \boxed{34} \text{ units} \]